2007
DOI: 10.1152/ajpheart.01372.2006
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β- and CTGF-mediated fibroblast recruitment influences early outward vein graft remodeling

Abstract: Luminal shearing forces have been shown to impact both geometric remodeling and the development of intimal hyperplasia. Less well studied is the influence of intramural wall stresses on vessel growth and adaptation. Using a vein graft-fistula configuration to isolate the impact of circumferential wall stress, we identify the reorganization of adventitial myofibroblasts as the dominant histological event that limits early outward remodeling of vein grafts in response to elevated wall stress. We hypothesize that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…11 Also critical may be the initial disequilibrium between cell proliferation and cell death, with several investigations confirming an early burst of apoptosis following vein graft implantation. 9,19 Contributing to this initial latency period may be a requirement for the systemic milieu to recognize and mount a response to perturbation. Specifically, the time-dependent behavior of vein graft thickening appears to be related to the biological process of leukocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Also critical may be the initial disequilibrium between cell proliferation and cell death, with several investigations confirming an early burst of apoptosis following vein graft implantation. 9,19 Contributing to this initial latency period may be a requirement for the systemic milieu to recognize and mount a response to perturbation. Specifically, the time-dependent behavior of vein graft thickening appears to be related to the biological process of leukocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies employed either systemic delivery of neutralising antibodies against the growth factors [21,25] or adenoviral gene delivery systemically or through the arterial lumen using vectors coordinating expression of soluble receptors to either PDGF-BB [23] or TGF-β1 [24,26]. More recently, connective tissue growth factor (CTGF) has also been implicated in enhanced adventitial myofibroblast activation and migration in a rabbit vein graft model of vascular remodelling [27] and may thus act as an additional profibrotic perivascular growth factor in synergism with TGF-β1 in the adventitia [28]. In a similar manner, vascular endothelial growth factor (VEGF) can enhance the activity of PDGF-BB to induce SMC migration and proliferation in vascular remodelling [29] and therefore represents another potential perivascular gene target.…”
Section: Growth Factors In Adventitial Myofibroblast Migrationmentioning
confidence: 99%
“…Previous studies have demonstrated that combining a fibrin glue scaffold with oligonucleotides antisense to PCNA results in a synergistic inhibitory effect on the intimal and medial hyperplasia characteristic of grafted veins (Jiang et al, 2007). This effect is associated with maintenance of blood vessel endothelium integrity, inhibition of PCNA expression, facilitation of smooth muscle cell migration, and formation of a new vascular network (Wan et al, 2006a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that regulation of the cell cycle and apoptosis involves a complex set of gene networks. During vein graft remodeling, several abnormal changes in these networks have been noted (Wan et al, 2006a,b;Jiang et al, 2007). Apoptosis has been shown to occur in in vitro cultures of vascular smooth muscle cells (VSMCs), as well as in in vivo arterial systems, and plays an important role in vascular remodeling.…”
Section: Introductionmentioning
confidence: 99%